Current Approaches to Herbal Drugs Application - L. Onchul (Zaslavsky O.Yu., 2016)
12 April in Kiev took place the press conference organized by the pharmaceutical company "Bionorica" - the unique manufacturer of pharmaceuticals with 80 years of world history. A scientific approach to the use of plants in medicine is the use of traditional herbal medicine and innovative technology. "Bionorica" belongs to an unprecedented concept of phytoneering, which connects the deciphering of the mechanisms of action of plant (PHYTO) and  innovative technologies and modern scientific methods (engineering). Presenting a harmonious blend of centuries-proven capabilities of medicinal plants with the highest technology, modern science and technology, the concept is very popular today.